A Brutal Examination: Russian Military Capability in Light of the Ukraine War. Issue 3 (4th May 2022) - Dalsjö, Robert; Jonsson, Michael; Norberg, Johan
Abstract: Russian armed forces' lacklustre performance in Ukraine has surprised military analysts. Shortcomings have included breakdowns in logistics, poor equipment and morale, abysmal communications, and muddled command and control, as well as a weak showing by the Russian Aerospace Forces, air defence, and cruise and ballistic missiles. Chief among the contributing factors are wishful political thinking, overreliance on esoteric doctrine and endemic corruption. War, however, brutally exposes peacetime cheating. Consequently, estimates of Russian military capabilities – in particular, for large-formation combined-arms operations, logistics, air defence and intangibles such as morale – need to be carefully reassessed. Earlier analyses of a Russia–NATO conflict appear to have overstated the challenge of defending Europe. Looking ahead, the conventional threat from Russia seems less daunting than previously thought, and the country faces a formidable task in repairing depleted capabilities. That said, President Vladimir Putin's appetite for risk is greater than anticipated.